Factors influencing rheumatology residents’ decision on future practice location - Shamis, Justin; Widdifield, Jessica; Batthish, Michelle; Mahendira, Dharini; Jamal, Shahin; Cividino, Alfred; Lethebe, B Cord; Barber, Claire (Canadian Medical Education Journal, 2020)
Background: There are regional disparities in the distribution of Canadian rheumatologists. The objective of this study was to identify factors impacting rheumatology residents’ postgraduate practice decisions to inform Canadian Rheumatology Association workforce recommendations. Methods: An online survey was developed, and invitations were sent to all current Canadian rheumatology residents in 2019 (n = 67). Differences between subgroups of respondents were examined using the Pearson χ2 test. Results: A total of 34 of 67 residents completed the survey. Seventy-three percent of residents planned to practice in the same province as their rheumatology training. The majority of residents (80%) ranked proximity to friends and family as the most important factor in planning. Half of participants had exposure to alternative modes of care delivery (e.g. telehealth) during their rheumatology training with fifteen completing a community rheumatology elective (44%). Conclusions: The majority of rheumatology residents report plans to practice in the same province as they trained, and close to home. Gaps in training include limited exposure to community electives in smaller centers, and training in telehealth and travelling clinics for underserviced populations. Our findings highlight the need for strategies to increase exposure of rheumatology trainees to underserved areas to help address the maldistribution of rheumatologists.